2009
DOI: 10.1111/j.1478-3231.2008.01921.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocytes as immune modulators in rotavirus‐induced murine biliary atresia

Abstract: Background/Aims Biliary atresia (BA) is a progressive disease characterized by bile duct inflammation and fibrosis. The aetiology is unknown and may be due to a virus-induced, autoimmune-mediated injury of cholangiocytes. Cholangiocytes are not only targets of injury but may also modulate hepatic inflammation. The aim of this study was to determine the immune profile of murine cholangiocytes and the ability to function as antigen-presenting cells (APCs) in culture with Rhesus rotavirus (RRV), poly I:C (viral m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 29 publications
1
47
1
Order By: Relevance
“…CD4 + and CD8 + T cell proliferation profiles induced by RRV-primed panDCs (and by cDCs alone for CD8 + cells) are consistent with the activating properties of DCs, a function previously attributed to cholangiocytes in livers from infants with biliary atresia (7, 17, 18). In view of recent work questioning this property of cholangiocytes (19), we cocultured a BALB/c-derived cholangiocyte cell line (mCL) infected with RRV with hepatic CD4 + or CD8 + T lymphocytes purified from control mice by means of a similar experimental strategy used for DCs. We found that cholangiocytes were unable to stimulate proliferation in lymphocytes (fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD4 + and CD8 + T cell proliferation profiles induced by RRV-primed panDCs (and by cDCs alone for CD8 + cells) are consistent with the activating properties of DCs, a function previously attributed to cholangiocytes in livers from infants with biliary atresia (7, 17, 18). In view of recent work questioning this property of cholangiocytes (19), we cocultured a BALB/c-derived cholangiocyte cell line (mCL) infected with RRV with hepatic CD4 + or CD8 + T lymphocytes purified from control mice by means of a similar experimental strategy used for DCs. We found that cholangiocytes were unable to stimulate proliferation in lymphocytes (fig.…”
Section: Resultsmentioning
confidence: 99%
“…When considering viruses as triggers of injury to bile ducts in neonates, α 2 β 1 integrins regulate RRV infection of cholangiocytes, an event that has been long viewed as key to the release of inflammatory signals and induction of lymphocyte proliferation (19, 24, 25). Contrary to this view, we did not find evidence for induction of lymphocyte proliferation by a cholangiocyte cell line infected with RRV.…”
Section: Discussionmentioning
confidence: 99%
“…Mack et al proposed that bile duct infection or injury due to rotavirus infection could be inciting factors leading to progressive, autoimmune-mediated damage of the biliary tree after recovery from infection (Mack & Sokol, 2005;Barnes et al, 2009). Incidentally, it has been revealed that programmed cell death in amphibian metamorphosis is induced by a selective auto-immune response, and that the immune system may contribute to the remodeling processes in vertebrate morphogenesis, universally (Mukaigasa et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In a series of experiments, investigators showed that RRV-infected cholangiocytes express both major histocompatibility complex (MHC) class I and aberrant MHC class II (21). Although they had all necessary markers for effective antigen presentation, cultured cholangiocytes were not shown to function as antigen-presenting cells in T-cell proliferation assays.…”
Section: Environmental Triggersmentioning
confidence: 99%